- #1

bugatti79

- 792

- 1

It looks correct via the codecogs website (https://latex.codecogs.com/eqneditor/editor.php)

\begin{align}

(S \circ R)^{-1} & = \left\{ \left< z, x \right> : \left< z, x \right> \in S \circ R \right\} \\

& = \left\{ \left< z, x \right> : \exists y \in Y s.t. \left< y, z \right> \in S, \left< x, y \right> \in R \right\} \\

&= \left\{ \left< z, x \right> : \exists y \in Y s.t. \left< z, y \right> \in S^{-1}, \left< y, x \right> \in R^{-1} \right\} \\

&= S^{-1} \circ R^{-1}

\end{align}